Pelatihan dan Pendampingan Pelaporan SPT Badan Menggunakan E-Form di PT. Sisfomedika Yogyakarta - Wendri Sukmarani; Maria Magdalena PD; Sapta Aji Sri Margiutom; Retno Sundari (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The Directorate General of Taxes issued announcement Number 10/PJ.09/2022 which requires business actors to report their annual corporate taxes using an E-Form, which previously business actors were more accustomed to using E-SPT. Annual corporate income tax reporting using the E-SPT is only valid until April 15, 2022, but seeing that business actors are still considered high for using the E-SPT, it is extended until May 1, 2022. The orientation of changing reporting from the E-SPT using the E-Form is one of the problems for business actors to be able to report the agency's Annual SPT at the reporting time determined by the Director General of Taxes. This will reduce the level of compliance of business actors in fulfilling their obligations to report the Annual Corporate SPT. PT. SISFOMEDIKA is a tax object of corporate income tax. In order to assist the government in increasing the compliance of business actors in completing tax obligations, especially reporting business entity income tax (Corporate Income Tax), training and assistance for reporting Corporate Income Tax of PT Sisfomedika Yogyakarta is carried out. Training and mentoring is carried out for 2 days, online training and online mentoring. The training process is a Build Up process to provide debriefing and the process of finding a Dilemma to be analyzed and provided assistance as a resolution and closing process in the form of reporting the 2021 annual corporate income tax as a result of this training and community service assistance. Evaluation Community service training and mentoring at PT Sisfomedika is felt to be more effective using the offline method, reporting using the E-Form from the results of a survey conducted after training and mentoring is felt to be easier than using the E-SPT.